Orientation towards social responsibility of North-West African firms - Sánchez-Hernandez, I.; Carvalho, L.; Paiva, I. (Sustainability Accounting, Management and Policy Journal, 2019)
Purpose Corporate social responsibility orientation (CSRO) is considered a crucial strategy to enhance long-term competitiveness around the world, and it is starting to be a broader issue in Africa. Based on recent works addressing the CSRO–performance relationship in countries outside the African continent, this paper aims to assess CRSO in North-West Africa. Design/methodology/approach In this study a questionnaire was distributed among 122 managers in two countries in North-West Africa: Guinea-Bissau and the Ivory Coast. Partial least squares (PLS) structural equation modelling (SEM) is used to assess the path or relationships for the North-West African context. Findings The results show that there is a generally positive perception of the economic, social and environmental dimensions of CSRO, although special emphasis is laid on the economic and social issues, mainly when they are related to human resources. The study also revealed the important role of innovation as mediator between CSRO and firm performance. Practical implications The study points out the role of managers in promoting a culture of social innovation by focussing on the CSR philosophy for improving the competitive success of African businesses. Social implications The social, economic and legal contexts of Guinea-Bissau and the Ivory Coast are vulnerable. The findings raise concerns about whether governments and regulatory efforts improve the development of the strategies towards social responsibility of African firms and whether they also increase the role of the firms in producing positive externalities to the market through CSRO. Originality/value Very few studies have investigated CSRO in Africa. Aiming to switch from the current CSRO in developed countries to an African perspective of CSRO, this paper contributes to filling the existing gap through the study of managers’ perceptions about CSR in two countries in North-West Africa: Guinea-Bissau and the Ivory Coast.